EXAMINING THE IMPACTS OF RELIGIOSITY, ATTITUDE, AND SUBJECTIVE NORM TOWARD INTENTION TO PURCHASE HALAL FOOD: A STUDY ON INDONESIAN MUSLIM CONSUMERS - Achsan, Titan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
This research aims to examine the impact of Religiosity, Attitude, and Subjective Norm Toward Intention to Purchase Halal Food. The type of this research is explanatory research that explains the causal relationship between variables by hypothesis testing. This research used the questionnaire and literature study to collect the data. Two hundred and ten (210) samples were used for this research requiring Muslim consumers in Surabaya to fill out the questionnaires. The sampling technique used was convenience sampling. Validity test, reliability test, and classical assumption test were the instruments used to test this research. The result of this research shows that Attitude has significant effect towards Intention to Purchase halal food, Subjective Norm has significant effect towards Intention to Purchase halal food, Inter-personal Religiosity has significant effect towards Intention to Purchase halal food, and Intra-Personal Religiosity has insignificant effect towards Intention to Purchase halal foods.Keywords: Intention to Purchase, Attitude, Subjective Norm, Religiosity, Halal Foods